Assessment of ant communities in secondary forest in the eastern Amazon - Harada, Ana Yoshi; Farias, Paulo Roberto Silva; Lopes, Letícia de Fátima Campos; Silva, Anderson Gonçalves da; Brandão, Alessandra Daniele de Sousa (Comunicata Scientiae, 2013)
Ant communities were assessed in plots fertilized with nitrogen and phosphorus in an area of secondary forest in the Eastern Amazon. Collections were made from April to September 2004, using the mini-Winkler extractor method. A total of 4893 ant individuals were obtained distributed in three subfamilies, 22 genera and 82 species. The most frequent species were Wasmannia auropunctata (100%), Pyramica sp1 and Solenopsis sp1 (75%). The Shannon diversity index showed low values, the Jaccard index presented dissimilarity, the equitability index showed that the distribution of the abundance of individuals was not homogeneous and the species richness also presented low values. There was variation in the composition of the ant fauna in soils fertilized with N, N + P and P. The study corroborated other research in degraded areas, showing that the species composition is modified compared to more complex environments. Avaliação das comunidades de formigas em floresta secundária na Amazônia Oriental Resumo Avaliaram-se comunidades de formigas, em parcelas fertilizadas com nitrogênio e fósforo emuma área de floresta secundária na Amazônia Oriental. As coletas ocorreram durante os mesesde abril e setembro de 2004, utilizando-se o método de extrator de mini-Winkler. Foram obtidos4893 indivíduos de formigas distribuídos em três subfamílias, 22 gêneros e 82 espécies. As espéciesmais freqüentes foram Wasmannia auropunctata (100%), Pyramica sp1 e Solenopsis sp1 (75%).O índice de diversidade de Shannon apontou baixos valores, o índice de Jaccard apresentoudissimilaridade, no índice de Equitabilidade verificou-se que a distribuição da abundância dosindivíduos não foi homogênea e a Riqueza de Espécies também apresentou baixos valores. Houvevariação na composição da fauna de formigas em solos fertilizados com N, N + P e P. O estudocorrobora com outras pesquisas em áreas degradadas, mostrando que a composição de espéciesé modificada quando comparadas com ambientes mais complexos.